Climate Change Awareness and Urban Food Choices: Exploring Motivations for Short Food Chain Engagement - Elena Kokthi; Fatmir Guri; Zenepe Dafku (Urban Science)
This study explores the relationship between climate change awareness (CCA) and consumers’ willingness to pay (WTP) for urban short food chains (USFC), focusing on the mediating role of biospheric, egoistic, and altruistic environmental concerns. A structured questionnaire was conducted with 230 respondents in Tirana, Albania, and the results were analysed using the PROCESS macro in SPSS 25.0. The findings reveal that CCA increases all three environmental concerns; however, only the altruistic concern significantly mediates USFC participation, particularly by limiting food waste (effect size = 0.502, p = 0.002). In contrast, egoistic concern negatively affects WTP, highlighting a value–action gap in sustainable behaviour. Reducing ultra-processed food consumption emerges as a key driver of engagement, linking personal and environmental health to local food choices. Gender moderates these relationships; despite showing high ecological concern, women express lower WTP due to household and budgetary considerations. Supporting the model, the survey data show that 88% of respondents are willing to pay a premium, typically 10–20% more, for food products from their preferred origin, and 88% are also willing to participate in the Tirana USFC initiative. The highest WTP (30%) is reported among highly educated women with children aged three to five. These findings highlight the need for targeted urban food policies that account for sustainability’s psychological and demographic dimensions.